E-delivery of personalised healthcare information to intermediaries for suicide prevention. (4th April 2005) - Wang, Ye Diana; Phillips-Wren, Gloria; Forgionne, Guisseppi
A novel use of store-forward telemedicine is described in which healthcare information is provided via internet-based information and communication technologies (ICTs) to an intermediary (a third-party observer) rather than directly to the patient to deliver suicide prevention e-healthcare. To be effective, information must be tailored specifically for each type of intermediary to enable improved decision making in interacting with the patient. The healthcare system filters data and delivers personalised healthcare information enabled by Internet-based ICTs for a specific type of user. An application to mental health is presented.